Perceived intrusiveness of rich media ads in online advertising: Evidences from young Indian travellers - Vinod Madhavan; Simon George; Gururaj Kidiyoor (Cogent Economics & Finance, 2019)
This paper examines the interrelated effects of perceived ad intrusiveness of rich media ads in online advertisements with respect to attitudes towards brands, online advertisement and the publisher's website on young Indian travellers. Despite the widespread use of the term in marketing literature, ad intrusiveness has received almost no attention in the destination marketing literature especially in the context of rich media ads. Data have been collected from 304 young Indian travellers using a structured questionnaire in an experimental design setting. Results indicate that perceived ad intrusiveness has direct and negative relationship on attitude towards brand, online advertisement and the publisher's website. Results suggest strategies that advertisers may adopt to minimize the negative influence of intrusiveness in case of direct response when compared to branding objectives. Various theoretical and managerial implications are discussed with directions for future research.
Keywords: M31; M37; Z31; Z33; 330; perceived intrusiveness; rich media ads; young Indian traveller; brand image; brand attitude; attitude towards website; reactance theory